2017
DOI: 10.1124/jpet.117.240721
|View full text |Cite
|
Sign up to set email alerts
|

Rational Tuning of Visual Cycle Modulator Pharmacodynamics

Abstract: Modulators of the visual cycle have been developed for treatment of various retinal disorders. These agents were designed to inhibit retinoid isomerase [retinal pigment epithelium-specific 65 kDa protein (RPE65)], the rate-limiting enzyme of the visual cycle, based on the idea that attenuation of visual pigment regeneration could reduce formation of toxic retinal conjugates. Of these agents, certain ones that contain primary amine groups can also reversibly form retinaldehyde Schiff base adducts, which contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 68 publications
2
27
0
Order By: Relevance
“… 51 – 53 Interestingly, the release of retinaldehydes during light exposure/daytime and thus the requirement for protection depends on Rpe65 activity. 54 , 55 Therefore, upregulation of Rdh12 during the daytime may be necessary to compensate for an Rpe65- dependent increase in retinaldehyde release.…”
Section: Discussionmentioning
confidence: 99%
“… 51 – 53 Interestingly, the release of retinaldehydes during light exposure/daytime and thus the requirement for protection depends on Rpe65 activity. 54 , 55 Therefore, upregulation of Rdh12 during the daytime may be necessary to compensate for an Rpe65- dependent increase in retinaldehyde release.…”
Section: Discussionmentioning
confidence: 99%
“…Emixustat (Figure 2 and Movie 2) is approximately ten times more potent than retinylamine in vitro (Zhang et al, 2015), is orally bioavailable (Kubota et al, 2014), and exerts specific effects on in vivo visual cycle activity as demonstrated in Phase 1 and 2 clinical trials (Dugel et al, 2015). It was shown that the potency of emixustat can be further improved by substitutions at the cyclohexyl moiety, for example in the molecule MB-004 (Kiser et al, 2017). Unfortunately, emixustat failed to demonstrate efficacy in the treatment of geographic atrophy as assessed in a large Phase 3 randomized, double-blind, placebocontrolled trial (Rosenfeld et al, 2018).…”
Section: Retinoid-based Treatment Of Retinal Diseasesmentioning
confidence: 99%
“…Interestingly, retinylamine/emixustat family molecules exhibit a second mechanism of action involving the direct sequestration of retinal released from bleached visual pigments, and this action plays a key role in the ability of these molecules to protect against light-induced retinal degeneration (Maeda et al, 2009;Zhang et al, 2015). Efforts are currently underway to develop retina-targeted retinaldehyde traps for treatment of diseases associated with formation of toxic retinaldehyde adducts (Kiser et al, 2017;Maeda et al, 2012).…”
Section: Retinoid-based Treatment Of Retinal Diseasesmentioning
confidence: 99%
“…enzyme of the visual cycle, based on the idea that an attenuation of visual pigment regeneration could reduce the formation of toxic retinal conjugates [19,20].…”
Section: Accepted Manuscriptmentioning
confidence: 99%